PENYULUHAN KESEHATAN DAN PERBANKAN SYARIAH DALAM MASA PANDEMI COVID-19 PADA DESA CIASMARA, KECAMATAN PAMIJAHAN, BOGOR - Rully Trihantana; Ria Kusumaningrum; Dhea Nurfauziah (SAHID DEVELOPMENT JOURNAL, 2022)
The Covid-19 pandemic in Indonesia has had a large socio-economic impact outside the healthsector. The impact is multi-sectoral and the effects will be visible in the long term – on the poorand vulnerable. The socio-economic impact of the pandemic on households is an important firststep that the government must take to help mitigate these impacts. Meanwhile, people now haveto adjust to the pattern of life in the era of the Covid-19 pandemic or better known as adaptingnew habits. This situation is no exception in Ciasmara Village, Pamijahan District, BogorRegency. Based on the analysis of the problems that occurred in the Ciasmara Village community,Pamijahan District, community service to the community in Ciasmara Village included conductingcounseling on the Covid-19 health protocol discipline and including counseling about shariabanking to the community to the taklim assembly and Micro, Small and Medium Enterprises.Through this community service activity, it is hoped that it can increase awareness and lifestylehabits of the community during the Covid-19 pandemic and also be enlightened and motivated intheir hearts and minds with Islamic banking values that are in line with Islamic teachings forresidents of Ciasmara Village, Pamijahan District, Regency Bogor.